The quintessence of breast leiomyosarcoma - Kalimuthu, Ashwini Kannamma; Viswanathan, Raja Senthil; Iyyappan, Ponniah; C., Kaliyappa (International Surgery Journal, 2018)
Sarcoma of the breast is a rare condition. The biological differences from other primary breast tumours necessitate a corresponding difference in approach to diagnostic and management strategies. The rarity of the condition has made clinicopathological study difficult. Authors report a case of primary leiomyosarcoma in a 40-yr-old-women, with a 15x9 cm bosselated swelling, involving all 4 quadrants of the left breast. Her clinical features, sonography and trucut biopsy were compatible with cystosarcoma phyllodes and she underwent a left mastectomy for the same. Later the histological and imunohistochemical studies established the diagnosis of leiomyosarcoma, grade 2.